Senior-Loken syndrome. Case reports of two siblings and association with sensorineural deafness. Issue 3 (March 1992) - Clarke, M P; Sullivan, T J; Francis, C; Baumal, R; Fenton, T; Pearce, W G
Abstract : Two siblings with Senior-Loken syndrome are described. The need for a full evaluation of renal function and hearing in children with a retinal dystrophy is emphasised.